Ab initio-guided development of super-hard Mo–Al–Cr–N coatings. (November 2017) - Klimashin, F.F.; Mayrhofer, P.H.
Abstract: The ab initio-guided adjustment in N2 -partial pressure during reactive magnetron sputtering allowed the preparation of single-phase cubic-structured Mo1 −  x  −  y Al x Cr y N z coatings with Al-contents up to even x  ≈ 0.6. Combining with low Cr-concentrations, Al-enrichment significantly enhances material strength. The highest hardness, H, of 41.2 ± 2.9 GPa in combination with a low indentation modulus, E, of 440 ± 15 GPa is obtained for Mo0.39 Al0.52 Cr0.09 N0.98, possessing also the highest H / E - and H 3 / E 2 -ratios of 0.1 and 0.36 GPa, respectively. Further Al-enrichment ( x  > ~ 0.6) favours, however, the hexagonal phase formation, drastically decreasing the hardness to ~ 20 GPa. Therefore, the combination of excellent mechanical properties with a high Al-content suggests fcc-Mo1 −  x  −  y Al x Cr y N z for severe applications. Graphical abstract: